Heterozygosity in LDLR rs2228671 and rs72658855 Gene is Associated with Increased Risk of Developing Coronary Artery Disease in India –A Case-Control Study - Jha, Chandan K.; Mir, Rashid; Banu, Shaheena; Elfaki, Imadeldin; Chahal, Sukh M.S. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2020)
Objective: Coronary artery disease (CAD) is one of the most common causes of death worldwide. Risk factors of CAD include high LDL-C, low high-density lipoprotein (HDL), hypertension, lack of exercise, genetic factors, etc. Polymorphisms of the LDLR gene have been associated with CAD in previous studies. Methods: The LDLR-rs72658855 C>T genotyping was detected by using allele-specific PCR (ASPCR). The association of rs2228671 and rs72658855 with CAD in a south Indian cohort (200 CAD patients and 200 matched healthy controls was studied. Results: Our findings showed that rs2228671 gene variability is associated with increased susceptibility to coronary artery disease in the codominant inheritance model for variant CC vs. CT OR 3.42(1.09-10.7), with P<0.034. A non-significant association was reported in the recessive inheritance model for the variant (CC+CT) vs. TT OR 0.56(0.16-1.95), at P<0.36. and in the dominant inheritance model for variant CC vs. (CT+TT) OR 2.8(1.07-7.34), at P<0.032 .In case of allelic comparison, it was indicated that the LDLR rs2228671-T allele was associated with an increased risk of developing CAD compared to C allele OR=2.4, with 95% CI (1.05-5.64) and P< 0.036 . Our findings showed that LDLR rs72658855 C>T gene variability was associated with an increased susceptibility to coronary artery disease in the codominant inheritance model for variant CC vs. CT OR 1.7(1.1-2.6), at P<0.015 and in the dominant inheritance model for variant CC vs. (CT+TT) OR 1.66(1.07-2.58), at P<0.0.02.. In case of allelic comparison, a non-significant association was reported in LDLR rs72658855-T and C allele. Conclusion: We concluded that the heterozygosity in LDLR-rs72658855 and rs2228671 and T allele in LDLR rs2228671 are strongly associated with increased susceptibility to coronary artery disease. These results must be validated by future well-designed studies with larger sample sizes and different populations.
Keywords: Peripheral Arterial Disease (PAD)